A case of suppurative arthritis of the temporomandibular joint - MIKI, Yukako; KUDO, Itsuro; KOMIYAMA, Kazuo; IWANARI, Shinkichi; FUKUYO, Shinho; ODA, Yasuyuki (Japanese Journal of Oral and Maxillofacial Surgery, 1997)
Suppurative arthritis usually occurs by hematogeneous dissemination of an infection localized in some other organ of the body. Much less frequently, bacteria may invade the joint either by direct spread of a neighboring infection or through a perforating injury. We reported an unusual case of suppurative arthritis in the left temporomandibular joint of a 53-year-old woman. The arthritis presented after a certain period after tooth extraction of the left lower 2nd molar tooth, and detachment of the cartilage cap. The joint was surgically removed because of resistance to long-term antibiotic therapy.